PENGUJIAN UNSUR PENYALAHGUNAAN WEWENANG PADA PERADILAN TATA USAHA NEGARA DALAM KAITANNYA DENGAN TINDAK PIDANA KORUPSI - Yasser, Bram Mohammad (Soumatera Law Review, 2019)
The testing of the Abuse of authority is an absolute thing in the determination of corruption crime and it causes the Financial Loss to the Country or the economy of the country, the Corruption crime that is intended in this case is in article 3 corruption eradication law ,that related to the authorities and goverment or the state administrators  especially in the use of state’s finance. the inception of Law No. 30 year 2014 about Government Administration has brought fundamental changes in the Organization of the Government substantially or procedurally in the use of authority by government officials, in which every policy made by public officials when there are indications of abuse of authority and financial harm the country or economy of the country, not must be brought directly into the realm of criminal acts of corruption through the Court of the crime of corruption, but rather should be tested first aspect of abuse of authority and the State's losses, though elements of his country's loss made by the Agency of the Financial Examiner (CPC).